Enhanced intestinal permeability in preterm babies with bloody stools. Issue 3 (March 1984) - Weaver, L T; Laker, M F; Nelson, R
Abstract : During a study of the intestinal permeability of newborn babies, three exhibited a sudden increase in lactulose absorption in association with the passage of bloody stools. An enhanced intestinal permeability may be an expression of the disruption of mucosal integrity in necrotising enterocolitis.